Evaluasi Faktor-faktor Yang Mempengaruhi Konsumen Dalam Keputusan Pembelian Perumahan Pondok Pesona Alam - M. Rizal Afrianto; Hammam Rofiqi Agustapraja (Universitas Negeri Gorontalo, 2020)
P.T. Widiantara Perdana Putra as a housing developer certainly wants to provide residential property products that could meet the needs and desires of the community. The developer find it difficult to identify the dominant factors affecting consumer decisions in choosing a type-25 house at Pondok Pesona Alam Housing (PPA). The purpose of this study is to determine the factors influencing the housing purchase decision. The sample used in this study were 25 PPA customers. A questionnaire were used to collect data. The analysis technique used is multiple linear regression. Based on the results of the analysis, it can be seen that the environment variable has a coefficient of 0.181 and is the most dominating of the other variables. Furthermore, the second variable is location with a coefficient of 0.173. While the third is the building variable with a coefficient of 0.146.